1984
DOI: 10.1073/pnas.81.8.2426
|View full text |Cite
|
Sign up to set email alerts
|

Increased adhesiveness of Down syndrome fetal fibroblasts in vitro.

Abstract: We compared the in vitro rate of divalent cation-independent aggregation of fibroblasts derived from abortuses with normal karyotypes and with trisomy 21 (Down syndrome). Fibroblasts from five lung and two of three cardiac cultures from subjects with Down syndrome aggregated more rapidly than matched fibroblasts from normal controls or lung fibroblasts from an abortus with trisomy 13. In contrast, skin fibroblasts derived from the trisomy 21 subjects had low rates of aggregation. The high rates of aggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…This congenital heart defect is characteristically associated with trisomy 21 in humans and with its animal equivalent (mouse trisomy 16) [Miyabara et al, 19821, suggesting that specific genetic factors are involved in the morphogenesis of ECD [Wright et al, 1984;Boughman et al, 19881. Analysis of clinical data suggested that ECD of the Certain associated CVMs are equally frequent in either Down or Ivemark syndrome, regardless of the presence of ECD. These associations may be influenced by yet undefined determinants of the syndrome itself.…”
Section: Discussionmentioning
confidence: 99%
“…This congenital heart defect is characteristically associated with trisomy 21 in humans and with its animal equivalent (mouse trisomy 16) [Miyabara et al, 19821, suggesting that specific genetic factors are involved in the morphogenesis of ECD [Wright et al, 1984;Boughman et al, 19881. Analysis of clinical data suggested that ECD of the Certain associated CVMs are equally frequent in either Down or Ivemark syndrome, regardless of the presence of ECD. These associations may be influenced by yet undefined determinants of the syndrome itself.…”
Section: Discussionmentioning
confidence: 99%
“…Against this idea, cellular adhesion is increased in fibroblasts obtained from Down syndrome patients. [60] Children with Down syndrome have a distinctive spectrum of heart malformations. They frequently have endocardial cushion defects but rarely have conotruncal or aortic arch abnormalities.…”
Section: Abnormalities Of Extracellular Matrixmentioning
confidence: 99%
“…Dramatic decreases in the expression of another Ig-CAM, NCAM, occur in cells of the endocardium during epithelial-mesenchymal transformation. 55,56 We speculate that the overexpression of DSCAM may have the potential to perturb epithelial-mesenchymal transformation and/or the migration and proliferation of mesenchyme cells, and possibly thus contribute to the increased intercellular adhesion seen in DS cushion fibroblasts 8 and the abnormal cushion development seen in DS-CHD. Further questions include whether DSCAM effects are mediated through homophilic adhesion, as suggested by recent studies in mouse fibroblasts 54 or through heterophilic adhesion and signaling interactions involving coreceptors and other cushion molecules.…”
Section: Dscam As a Candidate For Ds-chdmentioning
confidence: 99%
“…html). Further, both the etiology of characteristic DS heart defects and the increased intercellular adhesiveness of DS cardiac fibroblasts 8 implicate disturbances in cell adhesion as underlying DS-CHD. Of the 64 known and predicted genes 20 identified in the narrowed DS-CHD candidate region to date, DSCAM is the only one which has been shown to mediate cell-cell adhesion.…”
Section: Dscam As a Candidate For Ds-chdmentioning
confidence: 99%
See 1 more Smart Citation